2008
DOI: 10.1128/aac.00904-08
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin MICs for Methicillin-Resistant Staphylococcus aureus Isolates Differ Based upon the Susceptibility Test Method Used

Abstract: ᰔRecent studies have questioned treatment of serious methicillinresistant Staphylococcus aureus (MRSA) infections with vancomycin because of treatment failures, despite vancomycin MICs in the susceptible category (MIC Յ 2 g/ml) (2, 3, 5, 6, 7). Some of these studies have used broth microdilution for determining vancomycin MICs (5), while others have used the Etest commercial product (AB Biodisk, Solna, Sweden) (2, 7). We sought to determine if substantive differences might result from using different susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 6 publications
6
68
1
Order By: Relevance
“…In a study by Prakash et al (263), 101 MRSA isolates were tested by agar dilution and microbroth MICs according to CLSI criteria as well as by standard vancomycin Etest performed with two different brands of Mueller-Hinton agar (BBL and Remel). While there was reasonable correlation between the CLSI agar dilution and broth microdilution methods, the Etest results were consistently one twofold dilution higher than results for the other methods, changing the modal vancomycin MIC from 1 g per ml (broth and agar dilution) to 2 g per ml (Etest) (263). Similar results were recently reported for 1,800 randomly selected MRSA isolates, where Etest MICs were 0.5 to 1.5 log 2 dilution steps higher than the reference broth MIC results (291).…”
Section: Visa and Vancomycin Mic Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Prakash et al (263), 101 MRSA isolates were tested by agar dilution and microbroth MICs according to CLSI criteria as well as by standard vancomycin Etest performed with two different brands of Mueller-Hinton agar (BBL and Remel). While there was reasonable correlation between the CLSI agar dilution and broth microdilution methods, the Etest results were consistently one twofold dilution higher than results for the other methods, changing the modal vancomycin MIC from 1 g per ml (broth and agar dilution) to 2 g per ml (Etest) (263). Similar results were recently reported for 1,800 randomly selected MRSA isolates, where Etest MICs were 0.5 to 1.5 log 2 dilution steps higher than the reference broth MIC results (291).…”
Section: Visa and Vancomycin Mic Testingmentioning
confidence: 99%
“…However, the change in breakpoints will not help detect heteroresistant strains with a vancomycin broth MIC of Յ2 g per ml. Additionally, given the potential for differences in the vancomycin MIC results based on the methodology used (263,291), a vancomycin broth MIC using reference methodology such as CLSI broth microdilution should be used as the definitive test for the definition of VISA.…”
Section: Vancomycin-intermediate Staphylococcus Aureus (Visa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Etest reported vancomycin MICs higher than those reported by the two broth microdilution assays. This was expected and has been described elsewhere (33,36). Etest strips contain a gradient of vancomycin concentrations, including an intermediate reading of 1.5 g/ml, as opposed to the broth microdilution assays, where the concentrations are in 2-fold increments.…”
Section: Figmentioning
confidence: 99%
“…13 It has been reported that vancomycin MICs generated by Etest were consistently one twofold dilution higher than those determined by Clinical and Laboratory Standards Institute (CLSI) broth dilution method. 14,15 In addition, the BHIA plates being recommended to screen the S. aureus reduced susceptibility to vancomycin in the CLSI. 16 Thus, we tested the susceptibility of the resistant mutants of S. aureus ATCC43300 by three different MIC-testing methods in this paper.…”
Section: Introductionmentioning
confidence: 99%